Alanine Aminotransferase is a Predictor of NAFLD Activity Score for Diagnosing Non-alcoholic Steatoehpatitis (Bangladesh Medical Journal, 2019)
Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder characterized by excessive triglyceride- accumulation in hepatocytes. NAFLD has a multifactorial etiology and a combination of environmental, genetic and metabolic factors play a role in the development of advanced disease. NAFLD consists of a wide spectrum of conditions, ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) which can progress to cirrhosis and hepatocellular carcinoma (HCC). Despite the high prevalence and severity of hepatic illness, NAFLD remains under diagnosed, because of few symptoms, lack of accurate laboratory markers. The accurate diagnosis of NASH remains dependent on specific histological parameters in liver biopsy. Although liver biopsy remains the ‘gold standard’, there are practical limitations, including costs and risks. There is an increasing requirement for simple, less invasive, highly accurate and affordable screening tools. Alanine aminotransferase (ALT) has been proposed as a noninvasive and available marker for assessment of NASH. A hospital based observational study was carried out for a period of two years in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Data were analyzed by SPSS version 16. Statistical inference were done by estimating distribution, Chi-square test and student’s t-test respectively. Fifty (50) patients were analysed.Twenty five were NASH and twenty five were simple steatosis. ALT in NASH group  were 97.0±51.5IU/L and insimple steatosis group were 55.5±28.6 IU/L. In NASH group 64%  of raised ALT had NASH . In Non-NASH group 16% of raised ALT had no NASH.There was significant difference in the NAFLD activity score for diagnosing NASH between elevated and normal ALT( P  value 0.001).Bangladesh Med J. 2019 May; 48 (2): 1-6